Pengaruh latihan dribble zig-zag dan dribble-T terhadap kemampuan menggiring bola pemain sepak bola di SSB PUMA Kabupaten Demak tahun 2020 (Universitas Negeri Semarang, 2021)
ABSTRACT This research is an experiment using the One Group Pretest-posttest design. The population in this study were 18 SSB PUMA Demak players. The sampling technique was total sampling and there were 2 variables in this study, namely the dribble zig-zag exercise and the -T dribble exercise. Data analysis using t-test statistics. . The instrument used in this study was a dribbling test instrument compiled by Subagyo Irianto, et al, which had a validity of 0.779 and a reliability of 0.559. The mean results of the initial test for group 1, namely the dribble t exercise, was 27.99 and the final test was 25.63. Meanwhile, the mean results of the initial test for group 2, namely the dribble zigzag exercise, was 27.67 and the final test was 26.0. From the test results, the difference between groups 1 and 2 shows the difference in dribble speed for the experimental group I and the experimental group II, the t-count value is 1.228 with a t-table value of 2.262 with a significance of 0.254 â‰¥ 0.05. So it can be explained that from the difference between the experimental group I and the difference between the experimental group II there is an influence on the dribble speed of the SSB PUMA Demak players. It can be seen that the results of the training analysis using the T dribble training method are better and more improved than the dribble zigzag training method. l